Exercise echocardiography for improved assessment of diastolic filling dynamics - Mads Fischer; Thomas Bonne; Magnus Bak Klaris; Emil Lenzing; Eric J. Stöhr; Jacob Bejder; Carsten Lundby; Nikolai B. Nordsborg; Lars Nybo (Experimental Physiology)
Abstract During exercise stress, heart rate (HR) increases to support cardiac output, which also reduces ventricular filling time. Although echocardiography is widely used to assess cardiac function, studies display conflicting data on the dynamic changes in the healthy trained and untrained heart during rest and acute exercise stress. To address these discrepancies, we tested a new echocardiography exercise protocol on two groups with significant differences in cardiorespiratory fitness. Ten untrained individuals with maximal oxygen uptake of 38 ± 8 ml/kg/min and 10 endurance‐trained athletes matched for body surface area but with higher maximal oxygen uptake (71 ± 5 ml/kg/min) were evaluated at rest, during semi‐recumbent cycling at 25 and 75 W and at a relative workload intensity eliciting a HR of 140 beats/min (HR140). Stroke volume was 36% higher in the trained at rest, and this difference increased during exercise to 42% at 25 W, 46% at 75 W and 63% at HR140 (all P < 0.05). In contrast, no group differences were found in markers of myocardial function (ventricular contraction and relaxation velocities) or other traditional echocardiographic measures of ventricular function at rest or exercise for a given HR. However, while similar at rest, diastolic and systolic function provided limited insight into differences between less fit and highly fit individuals. The new exercise echocardiography protocol improves the ability to uncover differences in dynamic changes in diastolic filling capacity that explain the previously reported higher end‐diastolic compliance in endurance‐trained athletes.